1997
DOI: 10.1161/01.cir.95.3.745
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation–Systolic Pressure Relation

Abstract: This contribution reviews the regulation of left ventricular pressure (LVP) fall by load and relates this regulation to left ventricular contractility. Load regulation of LVP fall has to be distinguished from neurohumoral regulation, from effects induced by arterial reflected waves and from long-term load effects on contractility. The response of LVP fall to a moderate elevation of systolic LVP is highly variable. It depends on the ratio between the actual systolic pressure and peak isovolumetric pressure, def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…While in healthy hearts small afterload elevations accelerate LV pressure fall and only marked afterload increases slow it, in failing hearts even slight increases in afterload may induce slower relaxation. At a similar systolic LV pressure, in failing hearts the relative load, defined as the ratio of systolic LV pressure to isovolumetric LV pressure, is higher, the afterload reserve is surpassed and afterload mismatch yields a pronounced slowing of LV pressure fall, compared with healthy hearts [10,31].…”
Section: Edlvp) B End Diastolic LV Dimensions (Edlvd)mentioning
confidence: 99%
See 1 more Smart Citation
“…While in healthy hearts small afterload elevations accelerate LV pressure fall and only marked afterload increases slow it, in failing hearts even slight increases in afterload may induce slower relaxation. At a similar systolic LV pressure, in failing hearts the relative load, defined as the ratio of systolic LV pressure to isovolumetric LV pressure, is higher, the afterload reserve is surpassed and afterload mismatch yields a pronounced slowing of LV pressure fall, compared with healthy hearts [10,31].…”
Section: Edlvp) B End Diastolic LV Dimensions (Edlvd)mentioning
confidence: 99%
“…In the present study, we analyzed biventricular hemodynamics, LV myosin heavy chain (MHC) protein isoforms, LV myocardial expression of genes involved in neurohumoral activation (angiotensin-converting enzyme and endothelin-1), extracellular matrix remodelling (tenascin-C gene expression and interstitial fibrosis) and apoptosis (TUNEL assay), 4 and 6 weeks after MCT injection. Hemodynamics were studied at baseline and in response to single-beat afterload elevations, which allow the detection of diastolic dysfunction that may not be evident during evaluation at rest, but is revealed during exercise or hemodynamic stress [9,10,19,20,26,48].…”
Section: Introductionmentioning
confidence: 99%
“…The preceding beat is control and the following beat is test heartbeat. The analysed intervention, therefore, was a selective alteration of afterload without changes in preload or long-term load history (Gillebert et al 1997). Systolic LVP of the first heartbeat following the intervention varied as a function of the extent of aortic constrictions.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…13 Both the horizontal and vertical positions of the J-shaped curve are dependent on the magnitude of the peak isovolumetric LV pressure and could be manipulated by inotropic interventions. 13,17 Moreover, Eichhorn et al demonstrated that relaxation became highly afterloaddependent with systolic dysfunction. 16 They demonstrated that R (the slope of the -to-end-systolic pressure relation) was flat when contractility was normal.…”
Section: Afterload-dependence Of Bfmentioning
confidence: 99%
“…16,17 Moreover, this method of analysis of LV relaxation was successfully applied to a tachycardia-induced heart failure model in dogs. 18 Therefore, in the present study we analyzed on a beat-to-beat basis in patients with both AF and impaired LV systolic function by means of the force (relaxation) -interval relationships, as well as afterload-dependence.…”
mentioning
confidence: 99%